A Box Full of Darkness. (May 2013) - Boyce-Tillman, June
This paper is based on a piano piece commissioned by the British and Ireland School of Feminist Theology (BISFT) for its anniversary conference. It interrogates the situations in which the sections of the piece were created through the lens of conceptions of failure. It explores religious experience and identity in mental health contexts and the development of groups associated with Feminist Theology over the past 20 years. It examines the repression of the feminine, the place of anger in religion and therapy and its relation to a theology of the crucifixion and the processes of forgiveness. It integrates poetry into its text and sets out the role of the arts in process theology.